The Impact of Youth Unemployment Due To Work Experience Required by Business Houses, Lusaka Zambia - Ananda Kumar Aroumougame (Khazanah Sosial, 2021)
Research papers looking deep into the causes of youth unemployment focus not only on the causes but solutions of the unemployment rate in Lusaka Zambia. The government of Zambia recognizes these challenges and has pledged to increase employment in general, and employment for youth in particular. So far, however, his initiative has not made the needed difference. Often in business life young people are not given the opportunity or opportunity to express their abilities in relation to the skills they have acquired while in college. This study uses quantitavie method. Result The Government of the Republic of Zambia has in many cases talked about reducing the unemployment rate but the question is what has been done about it? More local flexibility in the design and implementation of policies to address youth unemployment could solve this problem. Participation in work operations results in gains in employment as income in the post-program period and decreases in welfare and unemployment receipts and payments. This positive effect persists at a relatively stable level for up to four years after youth leave the program.